Method treatment for decorative facade/ornamentation on shop houses / Ku Anita Tuan Yusoff - Tuan Yusoff, Ku Anita (Faculty of Architecture, Planning and Surveying, 2009)
Shop houses date back for many years and many are in relatively poor condition yet they resemble a distinctive look and style influenced by certain architectural background ranging from the pre-colonial years through colonial times and later to the independence o f Malaysia. The fafade which is a ‘statement’ of the shop houses, other than giving the artistic view, is a very important element in shop houses. Nevertheless, no matter how interesting it looks and tedious work molding the shape or carving, it receives the same deterioration/defects over the years. In respect to the heritage value, there are different ways for the treatment of defects and conservation to regain the budding and high level of authenticity. For that reason this dissertation is to identify common defects, causes, treatment and constraints, as well as the alternative ways to overcome the constraint or satisfying way to maintain a degree of authenticity on the treated fa?ade of shop houses. In achieving the objective of this dissertation, a compilation of data was collected from the survey questionnaire that was created from the pilot studies that derive from a few of case studies. From the data collected, it was then being analyze and findings were determined which later derive the conclusion of the dissertation.